2020
DOI: 10.1111/jcmm.15166
|View full text |Cite
|
Sign up to set email alerts
|

A network pharmacology‐based approach to explore the effects of Chaihu Shugan powder on a non‐alcoholic fatty liver rat model through nuclear receptors

Abstract: The pathogenesis of non-alcoholic fatty liver disease (NAFLD) is still not fully understood, and currently, no effective pharmacotherapy is available. Nuclear receptors (NRs) are important biological participants in NAFLD that exhibit great therapeutic potential. Chaihu Shugan powder (CSP) is a traditional Chinese medicine (TCM) formula that has a wide therapeutic spectrum including NAFLD, but the effective components and functional mechanisms of CSP are unclear. We adopted a network pharmacology approach usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 43 publications
4
18
0
Order By: Relevance
“…Accordingly, they proposed using Gremlin 1 as a biomarker and potential therapeutic target in complications of obesity such as NASH [ 35 ]. In addition, Nie et al proposed that PPARγ and RARα mRNAs are down-regulated in the NAFLD rat model [ 36 ]. Similarly, Pirola et al found that miR-122, miR-192 and miR-375 miRNAs were up-regulated in simple steatosis and even more so in NASH cases [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, they proposed using Gremlin 1 as a biomarker and potential therapeutic target in complications of obesity such as NASH [ 35 ]. In addition, Nie et al proposed that PPARγ and RARα mRNAs are down-regulated in the NAFLD rat model [ 36 ]. Similarly, Pirola et al found that miR-122, miR-192 and miR-375 miRNAs were up-regulated in simple steatosis and even more so in NASH cases [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, gallic acid (source: Shaoyao), oxidized paeoniflorin (source: Shaoyao), paeoniflorin (source: Shaoyao), paeoniflorin (source: Shaoyao), glycyrrhizin (source: Gancao), naringin (source: Chenpi, Zhiqiao), hesperidin (source: Chenpi, Zhiqiao), and ferulic acid (source: Chuanxiong) had higher contents, all above 1000 mg/g [ 28 ]. Although some studies have comprehensively elucidated the treatment of depression [ 6 , 29 ], nonalcoholic fatty liver disease [ 30 , 31 ] and functional dyspepsia [ 5 ] by Chaihu-Shugan-San, no studies have comprehensively elucidated the mechanism of Chaihu-Shugan-San in the treatment of breast cancer. Therefore, with the aid of network pharmacology, this study analyzed the specific molecular mechanism of Chaihu-Shugan-San in the treatment of breast cancer from a microscopic perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Through a network pharmacological approach Nie et al [ 262 ] highlighted that Chaihu shugan powder (CSP) may exert its beneficial effects against NAFLD through the interaction of its main compounds with nuclear receptors. Through a molecular docking approach, they screened PPARγ, FXR, PPARα, RARα and PPARδ and quercetin, kaempferol, naringenin, isorhamnetin and nobiletin interactions.…”
Section: Flavonolsmentioning
confidence: 99%
“…The NAFLD-induced rats treated with CSP exhibited ameliorated effects in body weight, hepatic histopathology and serum and liver lipids. Moreover, the mRNA levels of Pparγ, FXR, Pparα and Rarα were modified suggesting nuclear receptors regulation as a potential molecular mechanism underlying the effects of CSP [ 262 ].…”
Section: Flavonolsmentioning
confidence: 99%